A comparative study of intraoperative analgesic consumption and recovery profile between sevoflurane- and propofol-based general anesthesia in adults - Ray, Abanish; Das, Debojyoti; Shaw, Sweta; Chakraborty, Soma; Laha, Arpita; Mandal, Mohanchandra (Asian Journal of Medical Sciences, 2023)
Background: Many researches were performed in the past to compare propofol and sevoflurane as sole anesthetics. While some studies have reported the advantages of propofol regarding better recovery profile and post-operative analgesic sparing effect, the contrast reporting does exist. Hence, there is a further need of research to explore recovery characteristics. Whether either of these two as sole anesthetics can yield any benefit regarding intraoperative analgesics consumption has not been evaluated. Aims and Objectives: The study primarily aimed at determining total analgesic consumption in the intraoperative period (primary outcome), between those receiving either sevoflurane or propofol for induction as well as maintenance of anesthesia. In addition, intraoperative hemodynamics (heart rate and mean arterial pressure) and recovery profile were compared. Materials and Methods: Total of 168 patients, aged 18–60 years, the American Society of Anesthesiologists’ physical status I/II, undergoing elective and emergency surgeries under general anesthesia for 2–3 h finally recruited. Patients were randomly allocated to receive either sevoflurane (group S, n=84) or propofol (group P, n=84) for both induction and maintenance. Anesthetics were titrated to achieve bispectral index (BIS) value of 60. For both the groups, additional fentanyl was considered aliquots of 25 mcg whenever the hemodynamics changes occurred despite maintaining BIS value in the above-mentioned range. Results: The total intraoperative analgesic consumption was found comparable in both groups of patients. Induction time (38 vs. 59 s) and emergence time (8 vs. 10 s, P<0.001) were found shorter in the propofol group than in sevoflurane. Aldrete score >9 was achieved earlier with propofol compared with sevoflurane (8.5 vs. 12 min). Conclusion: Propofol-based shows no advantage over sevoflurane in view of intraoperative consumption of analgesics and intraoperative hemodynamic stability. However, the use of propofol was associated with faster induction as well as quicker emergence from anesthesia.